The global ammonia industry in transition: global market trends, price interdependencies, and techno-economic feasibility of green ammonia - Ofori-Bah, Catherine Obiribea (My University, 2025)
Ammonia is one of the most produced chemicals in the world, playing an essential role in global agriculture and industry. Traditionally produced using energy-intensive methods that are reliant on fossil fuels, ammonia’s market dynamics are influenced by energy prices and sustainability concerns. Additionally, concerns about a growing global population emphasized the importance of ammonia in crop production to meet global food demand. This dissertation explores the global ammonia market structure, analyzes the interdependencies between natural gas, ammonia, and agricultural commodity prices, and studies the techno-economic feasibility of local wind-powered ammonia production in Western Kansas over a 25-year lifespan. A desk review was used to explore the global ammonia market. Meanwhile, a Vector Error Correction Model (VECM) was used in the analysis of commodity price data from 2014 to 2024 to assess price transmissions. Subsequently, this dissertation reviewed the technologies required for wind-powered ammonia production and their associated costs. It also evaluated Net Present Value (NPV), Profitability Index (PI), Internal Rate of Return (IRR), Payback Period (PBP), and Return on Investment (ROI) for green ammonia production via four electrolysis technologies (i.e., alkaline water electrolysis (AWE), proton exchange membrane/polymer-electrolyte membrane (PEM), Anion exchange membrane (AEM), and Solid Oxide Electrolysis Cell (SOEC)) and four ammonia price scenarios (i.e. forecasted price series, average price from 2014 to 2021 ($647.81/MT), average price from 2022 to 2024 ($1160.78/MT), and the highest ammonia price ($1770.42/MT)). Sensitivity analysis was conducted to examine the impact of changes in electrolyzer efficiency and ammonia market prices on NPV. Market analysis showed an increasing interest in transitioning from fossil-based ammonia to green ammonia. Furthermore, the results show that there is a cointegrating relationship between natural gas and ammonia prices, as well as ammonia prices and agricultural commodities. The technoeconomic feasibility studies revealed that under current cost and efficiency levels, the project is not economically feasible. Green ammonia production is economically feasible under all wind-electrolyzer combinations at an average price of $1160.78/MT and at the fixed highest price scenario. Sensitivity analyses revealed that green ammonia production can become competitive with conventional production with increased electrolyzer efficiencies and unusually high prices for conventional ammonia. This dissertation provides an integrated view of the ammonia market, price, and production dynamics, offering insights for navigating a transition from conventional ammonia production to green ammonia production. This research further contributes to the literature on renewable-based pathways for industrial decarbonization.
Keywords: Green ammonia; Techno-economic feasibility; Renewable energy; Price interdependencies; Cointegration; VECM